Effect of the initial population density of the Meloidogyne javanica nematode on the growth and grain yield of soybean - Sharma, Ravi Datt; C., Luis Hernán Rodríguez (Pesquisa Agropecuaria Brasileira, 2014)
Relationship between initial population densities (Pi) of Meloidogyne javanica (Treub 1885) (Chitwood 1949) and the growth and grain yield of soybean cv. UFV-1 and final population densities was investigated under greenhouse conditions. Two-day old plants grown in 2 kg of soil (1:1 mixture of Dark-Red Latosol and river sand) were inoculated with 0, 2, 4, 8, 16, 32 and 64 larvae per g of soil. A highly significant correlation (P <0.05%) between P. and means of plant height, fresh weight of aerial part, root, and leaf area of the plant after 35, 70 and 95 days of inoculations observed. With the increase in P levels from zero to 2, 4, 8 and 16 larvae per g of soil, the percent reduction in grain yield was 43.5, 52.1, 82.4 and 98 respectively. There was significant linear relationship between Pi and Pf up to 16 larvae per g of soil. The final population (Pf) was high more than five larvae per plant at the treatment with four-larvae per g of soil initial population, and the lowest (zero) at 32 and 64 larvae per g of soil.